Kehendak Untuk Berkuasa Dan Manusia Unggul Dalam Perspektif Friedrich Nietzche - Luh Putu Santi Pradnyayanti; Desak Made Ayu Indri Safira (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2021)
For humans, knowing who he is and where he came from, what is the purpose of his life, how he lives life consistently, is a different matter. The question of "who is that human?" is the most basic and most important question in human history. All questions concerning other things, such as about the earth, moon, sky, air, water, and atoms, cells and about God are only relevant if they are related to humans. However, all these questions are one unit, namely related to the meaning of life and the values of human existence. Nietzsche explores strongly the discourse on existentialism issues (freedom, death, fear, worry, human suffering). Nietzsche's doctrine stems from a concrete understanding of man and his life. Nietzsche's main teaching was the will toward attainable power in the idea of the ideal superior human. This asserts that human existence is a human will wish that transcends comparison. Nietzsche is a spirit beyond his time (modern rationality). The way to achieve human excellence with three basic components, namely courage, intelligence and pride. Humans must be brave to face life, both happiness and suffering. Nietzsche asserts that with suffering, humans will reach their maximum potential, because when we are faced with conflict, humans can release all potential and abilities that will help him to become Ubermensch. Keywords: Human, superior human, human existence